Ocular Manifestations in Systemic Lupus Erythematosus - Ade J. Nursalim; Enricco H. Mamuaja; Wenny Supit; Elbetty Simanjuntak; Stevanus J. Loho; Christian M. Komaling (Universitas Sam Ratulangi, 2022)
Abstract: Systemic Lupus erythematosus (SLE) is a connective tissue disorder that attacks several organs of the body, including the eyes. Ocular manifestation of this disease could be a sign of SLE activity and can cause decreased vision function to blindness. SLE can also affect extraocular tissue, anterior segment, posterior segment, and the optic nerve. The assessment of eye abnormalities that may arise due to SLE should alert the ophthalmologists. Treatment can be either local or systematic. The systematic management includes antimalarial agent, corticosteroids, immunomodulators, and biological agents. Cooperation among divisions and other medical fields is needed in the treatment of SLE. This paper aims to present the ocular manifestations of SLE, and is expected to improve the diagnostic quality, especially in terms of early diagnosis and appropriate treatment.Keywords: systemic lupus erythematosus; ocular manifestationÂ Abstrak: Sistemik lupus eritematosus merupakan kelainan jaringan ikat yang yang menyerang beberapa organ tubuh termasuk mata. Gangguan pada mata ini dapat menjadi tanda keaktifan SLE, dan menyebabkan penurunan fungsi penglihatan hingga kebutaan. SLE dapat memengaruhi jaringan ekstraokular, segmen anterior, segmen posterior, dan saraf optik. Pengkajian kelainan mata yang mungkin timbul akibat SLE ini perlu mendapat perhatian oleh dokter mata. Tatalaksana dapat berupa tatalaksana lokal maupun sistemik. Tatalaksana sistemik berupa obat-obatan anti malaria, kortikosteroid, imunomodulator, dan agen biologis. Kerjasama antar divisi dan bidang kedokteran lainnya diperlukan dalam penanganan SLE. Tulisan ini bertujuan untuk menge-mukakan manfestasi klinis SLE pada mata dan diharapkan dapat meningkatkan kualitas diagnostik terutama dalam hal diagnosis dini dan tatalaksana yang cepat dan tepat.Kata kunci: sistemik lupus eritematosus; manifestasi okular